2018
DOI: 10.1080/14763141.2018.1429489
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and kinetic differences between left-and right-handed professional baseball pitchers

Abstract: While 10% of the general population is left-handed, 27% of professional baseball pitchers are left-handed. Biomechanical differences between left- and right-handed college pitchers have been previously reported, but these differences have yet to be examined at the professional level. Therefore, the purpose of this study was to compare pitching biomechanics between left- and right-handed professional pitchers. It was hypothesised that there would be significant kinematic and kinetic differences between these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…1012 Furthermore, unlike other sports, baseball has very different sport characteristics depending on its play position. 13 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1012 Furthermore, unlike other sports, baseball has very different sport characteristics depending on its play position. 13 15…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Furthermore, unlike other sports, baseball has very different sport characteristics depending on its play position. [13][14][15] The purpose of this study is to analyze the correlation between YBT scores and ankle injury and assess differences in YBT scores between different baseball positions. We assume that the reference values of YBT will vary depending on the position of the baseball players.…”
Section: Introductionmentioning
confidence: 99%
“…Left-handed collegiate and professional pitchers have been noted to have shorter stride widths compared with their right-handed counterparts. 11 Pitch type has also been shown to have varying stride width, with curveballs associated with shorter stride widths relative to fastballs. 12,16 Stride width has also been shown to decrease as pitchers increase in playing level.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the higher throwing velocity among right-handed players observed here, and elsewhere, could be that lefties and righties differ in their underlying throwing mechanics. In fact, in an attempt to understand what might be contributing to the disproportionate number of left-handed pitchers, previous research has shown that left- and right-handed pitchers differ significantly in key kinematic parameters both at the collegiate (e.g., Werner et al, 2010) and professional level (Diffendaffer, Fleisig, Ivey, & Aune, 2019). Among professionals, for example, right-handed pitchers show greater landing position of the stride foot, trunk separation at foot contact, maximum shoulder external rotation, and trunk forward tilt at ball release.…”
Section: Discussionmentioning
confidence: 99%